O femirracídio em notícias: um estudo discursivo e sociocognitivo - Natale, Raquelli (2020)
Despite all efforts and advances in the creation of laws that precede the prevention, combat and punishment of crimes against women in Brazil, until the last few years the rate of feminicide continues to grow, which show one of the serious problems that B